(untitled) (Bulletin of the International Association for Paleodontology, 2020)
Introduction: In Forensic Medicine, the estimation of the stature often has a crucial role in the reconstructive phase of disjointed populations. The femur, being the longest bone in the human body, is usually the most reliable source in height estimation. However, in these populations, intact femurs are hardly ever found, making it necessary to use femur fragments for the same purpose. Aim: This investigation aims to estimate the stature of the catastrophic population concerning the earthquake that occurred in Lisbon, in 1755. Materials and Methods: The study was conducted on 8 whole femurs and 21 fragments, which were measured and weighted. These measurements were applied in a regression formula, obtained from the gathered research, in order to estimate the stature of the population. Results: The results showed that, for the whole femur, the correspondent height varies between 147.96 cm and 168.82 cm. For the fragments, the obtained estimates vary between 151,96 cm and 174.96 cm. Conclusions: The methods used proved to be reliable in estimating the length of the femur, as well as in deducting the height of individuals through this bone, allowing the study of these parameter’s evolution in generations.